“In his Native Land, a Dweller from afar…”: Vasily Selivanov – Discoveries and Poetics of His Works - Snežko, Julija (Literatūra, 2025)
In this article, the poetics of the Vilnius poet Vasily Selivanov (1902–1925), whose 100-year-anniversary of death is marked in 2025, is analysed. Only one poetry collection “The Shroud” (1928) was published during his lifetime. The present study considers newly discovered manuscripts containing previously unpublished poems by Selivanov (several of which are being published here for the first time). The author demonstrates that the themes of exile and nostalgia – dominating Selivanov’s works and providing basis for his characterization as a poet of ‘emigrant despair’, as proposed by P. Lavrinets – are also embedded within a symbolist poetics, ‘diabolic’ and mythopoetic elements of which are clearly present in his poems (motifs of dark and light suffering, longing for the ‘other’, dreams, silence, nature, and the city). At the same time, this symbolist stratum frequently coexists with landscape imagery and meditative reflection that capture the inner state of the poet or nature. Selivanov’s poems demonstrate both stylistic and internal unity.